TRANSLATION OF RELIGIOUS TEXTS PROBLEMS AND SPECIFICITIES - Abdualimova Lobar G’aybulla qizi (TADQIQOTLAR, 2025)
Annotation. This article discusses the main problems in translating religious texts,  including  lexical,  semantic,  cultural,  doctrinal,  and  interpretive  challenges.  It highlights the difficulties translators face in conveying the sacredness and doctrinal accuracy of religious texts into different languages.